2007
DOI: 10.1634/theoncologist.12-1-38
|View full text |Cite
|
Sign up to set email alerts
|

The Continuum of Care: A Paradigm for the Management of Metastatic Colorectal Cancer

Abstract: LEARNING OBJECTIVESAfter completing this course, the reader should be able to:1. Discuss recent progress in the treatment of patients with advanced colorectal cancer.2. Define the continuum-of-care approach and how it may differ from our current approach to the treatment of patients with advanced colorectal cancer.3. Identify key factors in treatment selection for patients with advanced colorectal cancer.4. Explain the impact of each active drug in the treatment of advanced colorectal cancer and the impact of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
164
0
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 217 publications
(172 citation statements)
references
References 38 publications
3
164
0
3
Order By: Relevance
“…The radioactivity was higher in the tumor than in other organs in the control group. A significant difference in the biodistribution of 18 F-FLT in the tumor was observed between the control and cetuximab-treated groups. Biodistributions in the control and cetuximab-treated groups were 0.098±0.005 (%ID/g) x kg and 0.029±0.010 (%ID/g) x kg, respectively (p<0.001).…”
Section: Resultsmentioning
confidence: 91%
See 4 more Smart Citations
“…The radioactivity was higher in the tumor than in other organs in the control group. A significant difference in the biodistribution of 18 F-FLT in the tumor was observed between the control and cetuximab-treated groups. Biodistributions in the control and cetuximab-treated groups were 0.098±0.005 (%ID/g) x kg and 0.029±0.010 (%ID/g) x kg, respectively (p<0.001).…”
Section: Resultsmentioning
confidence: 91%
“…Biodistribution of 18 F-FLT. The biodistribution of 18 F-FLT in the ex vivo study group on day 3 is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations